e-JIKEI Network using e-JIKEI Cameras: Community security using considerable number of cheap stand-alone cameras - Fujii, Yusaku; Maru, Koichi; Kobayashi, Kojiro; Yoshiura, Noriaki; Ohta, Naoya; Ueda, Hiroshi; Yupapin, Preecha (My University, 2010)
The e-JIKEI Network, a concept for realizing a safer and more comfortable community, and the e-JIKEI Camera, a stand-alone camera developed for the e-JIKEI Network, are reviewed. The concept of the e-JIKEI Network is that residents view their surroundings using cheap cameras, which act as their eyes, and home computers, which act as their brains, using the free software provided by us through the Internet. For the complete protection of the privacy of ordinary citizens, we propose a second concept supporting the concept of the e-JIKEI Network; in this concept, those who own and manage images (owners) and those who have the right to view these images (viewers) are separated by means of image encryption. Since 2004, the " Dairi-EYE" series, a free software for a personal computer (PC)-based system, has been distributed through our website. However, the use of PCs is not very user-friendly. Therefore, an all-in-one device called the " e-JIKEI Camera" has been developed. A social experiment of the e-JIKEI Network using e-JIKEI Cameras has been carried out. © 2010 Elsevier Ltd.
Keywords: Community safety; Crime prevention; Internet; Privacy; Security camera